Highly porous, low band-gap NixMn3−xO4 (0.55 ≤ x ≤ 1.2) spinel nanoparticles with in situ coated carbon as advanced cathode materials for zinc-ion batteries. Issue 30 (9th July 2019) - Long, Jun; Gu, Jinxing; Yang, Zhanhong; Mao, Jianfeng; Hao, Junnan; Chen, Zhongfang; Guo, Zaiping
Abstract : Aqueous zinc ion batteries (ZIBs) are emerging as a highly promising alternative technology for grid-scale applications where high safety, environmental-friendliness, and high specific capacities are needed. Abstract : Aqueous zinc ion batteries (ZIBs) are emerging as a highly promising alternative technology for grid-scale applications where high safety, environmental-friendliness, and high specific capacities are needed. It remains a significant challenge, however, to develop a cathode with a high rate capability and long-term cycling stability. Here, we demonstrate diffusion-controlled behavior in the intercalation of zinc ions into highly porous, Mn 4+ -rich, and low-band-gap Ni x Mn3− x O4 nano-particles with a carbon matrix formed in situ (with the composite denoted as Ni x Mn3− x O4 @C, x = 1), which exhibits superior rate capability (139.7 and 98.5 mA h g −1 at 50 and 1200 mA g −1, respectively) and outstanding cycling stability (128.8 mA h g −1 remaining at 400 mA g −1 after 850 cycles). Based on the obtained experimental results and density functional theory (DFT) calculations, cation-site Ni substitution combined with a sufficient doping concentration can decrease the band gap and effectively improve the electronic conductivity in the crystal. Furthermore, the amorphous carbon shell and highly porous Mn 4+ -rich structure lead to fast electron transport and short Zn 2+ diffusion paths in a mild aqueous electrolyte. This study provides an example of a technique to optimize cathode materials for high-performance rechargeable ZIBs and design advanced intercalation-type materials for other energy storage devices.